The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1097/tgr.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Support Role in Occupational Therapy Video Telehealth

Megan E. Gately,
Emily E. Metcalf,
Dylan E. Waller
et al.

Abstract: Caregiver involvement may facilitate patient participation in occupational therapy (OT) video telehealth. However, little is known about the extent to which caregivers participate and what they do. This scoping review aims to: (1) describe the caregiver role supporting patient participation in OT video telehealth and (2) identify barriers and facilitators to caregiver involvement. Findings reveal caregiver involvement in a range of OT evaluation and intervention processes, with details on what caregivers did o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…Specifically, the interview results that informed survey items were those about (1) patients for whom caregivers tended to be involved in video appointments, which informed the survey item about patient factors contributing to caregiver involvement; (2) what caregivers did during video telehealth visits, which informed survey items about the technological and clinical tasks with which caregivers assisted; and (3) how caregiver involvement enhanced the video sessions, which informed the survey item about the perceived benefits of caregiver participation. Second, we conducted a scoping review concerning caregivers' support role in OT video telehealth [27]. The scoping review results that informed survey items related to caregiver roles and the types of tasks caregivers assist with during video telehealth visits.…”
Section: Survey Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the interview results that informed survey items were those about (1) patients for whom caregivers tended to be involved in video appointments, which informed the survey item about patient factors contributing to caregiver involvement; (2) what caregivers did during video telehealth visits, which informed survey items about the technological and clinical tasks with which caregivers assisted; and (3) how caregiver involvement enhanced the video sessions, which informed the survey item about the perceived benefits of caregiver participation. Second, we conducted a scoping review concerning caregivers' support role in OT video telehealth [27]. The scoping review results that informed survey items related to caregiver roles and the types of tasks caregivers assist with during video telehealth visits.…”
Section: Survey Developmentmentioning
confidence: 99%
“…The lowest reported clinical tasks caregivers assisted with related to hands-on aspects of evaluation and intervention, reflecting a gap in the literature about caregivers' role in OT video sessions and in dynamic assessment more broadly. Our recent scoping review of caregivers' support role in OT video sessions indicated that although caregivers are often mentioned as being involved in evaluation and intervention, information about the level of caregiver involvement (ie, whether they physically assisted patients or the types of assistance they provided) was generally lacking [27]. This points to a potential lost opportunity in that caregivers may be able to assist remote clinicians during video sessions by setting up the environment, operating the camera, or providing standby supervision.…”
Section: Caregiver Assistance With Clinical Tasks During In-home Vide...mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing aging population has created a demand for e-health technologies that support healthy aging, reduce health care costs, and address the limited availability of health care professionals 1,2. These technologies encompass various information and communication technologies used in health care settings, including remote monitoring technologies (RMTs) 3-5. RMTs allow for the remote monitoring of individuals' health and the transmission of data to health care providers for review.…”
mentioning
confidence: 99%